COMPARISON OF COMPLICATIONS OF ENDOSCOPIC THIRD VENTRICULOSTOMY (ETV) VERSUS VENTRICULOPERATIONEAL SHUNT AMONG CHILDREN WITH NON-COMMUNICATING HYDROCEPHALUS - HUSSAIN, MA; ULLAH, MN; KASHIF, I; SAFDAR, S; IBRAHIM, M (Biological and Clinical Sciences Research Journal, 2024)
The outcome of congenital obstructive hydrocephalus in children, such as surgical complications, neurologic sequelae, and academic achievements, have been the subject of concern in the reported literature. However, much controversy still exists in terms of long-term as well as social outcomes and predictors of various complications and desired clinical outcomes. Objective: To compare complications of Endoscopic third ventriculostomy (ETV) versus ventriculoperitoneal shunt among children with non-communicating hydrocephalus. Methods: This Quasi-experimental study was conducted at the Department of Neurosurgery, Nishtar Medical University, Multan. Group A patients undergoing Endoscopic third ventriculostomy and Group B patients undergoing Ventriculoperitoneal Shunt (medium pressure Medtronic shunt bur hole type) were taken. Patients were kept in the ward postoperatively until considered fit and discharged on the 5th postoperative day. The first follow-up visit was on the 7th day after discharge; the second follow-up was at one month, and the subsequent follow-up was every three months for one year and shall be recorded on Proforma. Result: 54 children with obstructive hydrocephalus were included in our study. Of these, 44 (81.5 %) were male, whereas only 10 (18.5%) were female. The mean age of our study cases was 12.94 ± 6.90 months (range; 6 months to 24 months) and 68. 5%(n=37) were aged up to 15 months. Of these 54 study cases, 46.3% (n=25) were residents of rural areas, while 53.7 % (n = 29) were from urban localities. Twenty-six (48.1%) patients were from poor social class, while 51.9% (n=28) were from middle-income families. Thirty-seven percent (n = 20) of mothers were illiterate, while 63% (n = 34) were literate. Complications were noted in 13 % (n = 7) patients, infection was reported in 3.7% (n= 2), seizures in 9.3% (n=5), and ICH in 3.7% (n=2). These groups, A and B, were comparable in gender, age, residential status, socioeconomic status, and maternal literacy, i.e. (P = 0.293, P = 0.998, P = 0.586, and P = 0.786, P = 0.779, respectively). Complications in group A (ETV) were noted to be 3.7% versus 22.2 % in group B (VP shunt) (P = 0.100). Conclusion: Endoscopic third ventriculostomy is a safe, effective, and reliable procedure for the management of congenital obstructive hydrocephalus in the pediatric population as compared with VP shunting. Endoscopic third ventriculostomy surgeries should be a treatment of choice among all treating Neurosurgeons to achieve successful outcomes and a high survival rate.